Context Clues Knowledge and Reading Comprehension Skills of Grade 10 Students - Jomocan, Cynthia O.; Legaspi, Ma. Judy B. (Philippine Social Science Journal, 2020)
One of the goals of education is to develop learners with strong reading and comprehension skills. Memorandum No. 173 s. 2019 of the Department of Education strongly encouraged all elementary and secondary public schools to intensify their advocacy for independence in reading in all grade levels and align the promotion of reading culture as the key in closing achievement gaps in producing productive citizens. It is a fact that many Filipino learners struggle to meet the standards in English communication and language. Given the literature gap, this study determined the level of context clues knowledge and level of reading comprehension skills of Grade 10 students in the three-class programs: Basic Education Curriculum (BEC), Science Technology (STE), and the Strengthened Technical Vocational Education Program (STVEP) of a public junior high school in the Division of Bacolod City. The study also determined the difference in the level of context clues knowledge and level of reading comprehension skills of the students when grouped according to class programs and explored the relationship between context clues knowledge and reading comprehension skills.